The Contribution of Self-Concept to assist Career Planning of Student - Gita Yandri Yetni; Mudjiran Mudjiran; Alwen Bentri (Universitas Negeri Padang, 2020)
This study aims to describe the contribution of self-concept to career planning. The study is to be descriptive with population class XI and XII in SMAN 1 V Koto Timur which totaled 272 students with samples of the study amounted to 162 students. The technique used in sampling uses stratified random sampling. The research instrument uses a Likert measurement scale model. The data obtained were analyzed using percentage techniques. The research findings show that self-concept: (1) the perceptual or physical self-concept are a picture of a person associated with physical appearance being in the category of high; (2) conceptual or psychological self-concept which is also called psychological self-concept is a picture of a person of himself, his abilities or disabilities, his future, and includes the quality of his life change, honesty, self-confidence, freedom, and courage on the category of high; (3) attitudinal is a component that involves how individuals weigh their feelings about themselves about individual attitudes now and also hopes are in the high category. Students still lack self-understanding related to their future. Ideally, students who have careful planning for their careers have positive self-concepts. The successes and failures of students in determining their career planning are closely related to students 'self-understanding, students' understanding of the environment and career information obtained from career guidance in their schools.